Phonon scattering mechanism in van der Waals heterostructures comprising of MoS2 and WS2 nanosheets. (2021) - Sinha, Sneha; Arora, Sunil K.; Wu, Han-Chun; Sathe, Vasant G.
Abstract: In this work, the effect of temperature on the phononic modes (E 1 2g and A1g ) of few-layered MoS2 and WS2 nanosheets and their van der Waals heterostructure has been investigated in the temperature regime: 80–600 K. The E 1 2g and A1g modes showed a red-shift with an increase in temperature and exhibited non-linear temperature dependency above 300 K for the constituent nanosheets and their co-stacked heterostructure. A physical model comprising of both thermal and volume effects, is used to quantitatively understand the origin of non-linear temperature dependency of E 1 2g and A1g modes. The observed non-linearities in the phononic modes is well described by the higher-order phonon scattering as a consequence of greater amount of sulphur vacancies in the nanosheets as compared to the bulk counterparts. However, the MoS2 -WS2 heterostructure exhibited higher structural stability (lesser sulphur vacancies) as compared to its constituent counterparts owing to the enhanced van der Waals coupling at the hetero-interface and subsequently it decreases with rise in temperature.